Surprises are the benefits: reframing in multidisciplinary design teams. (November 2016) - Stompff, Guido; Smulders, Frido; Henze, Lilian
Abstract : This paper explores the social dimension of collaborative design from the perspective of Schön's reflective practice. An in-depth video protocol study was performed on the reflective practice in an experienced design team. It looks, in particular, at reframing: the process to find a new productive frame for subsequent activities. Reframing processes are amplified in a social context, requiring considerable time and effort on the part of design teams. Reframing has distinctive features that set it apart from other steps of reflective practice. Two iterative stages are discerned: sensemaking, to reconstruct prior operating frames; and future framing, to design a frame for future activities. Surprises incite reframing, and we argue that surprises are a source for team learning and innovation. Highlights: Schön's theories fit the practice of multidisciplinary design teams well. For teams, reframing processes require considerable time and a distinctive process. Two stages are discerned: sensemaking and future framing. Surprises incite reframing, and thus lead to team learning and innovation.